2020
DOI: 10.1093/nar/gkaa004
|View full text |Cite
|
Sign up to set email alerts
|

BHi-Cect: a top-down algorithm for identifying the multi-scale hierarchical structure of chromosomes

Abstract: High-throughput chromosome conformation capture (Hi-C) technology enables the investigation of genome-wide interactions among chromosome loci. Current algorithms focus on topologically associating domains (TADs), that are contiguous clusters along the genome coordinate, to describe the hierarchical structure of chromosomes. However, high resolution Hi-C displays a variety of interaction patterns beyond what current TAD detection methods can capture. Here, we present BHi-Cect, a novel top-down algorithm that fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that TADs forming into a hierarchical structure inside. These hierarchical domains have been defined as ‘metaTADs’ [13] or ‘sub-TADs’ [24] , [25] , [26] , [27] . Even in a single cell, Zhuang’s lab observed TADs and a sub-TAD-like structure by multiplexed super-resolution fluorescence in situ hybridization imaging [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that TADs forming into a hierarchical structure inside. These hierarchical domains have been defined as ‘metaTADs’ [13] or ‘sub-TADs’ [24] , [25] , [26] , [27] . Even in a single cell, Zhuang’s lab observed TADs and a sub-TAD-like structure by multiplexed super-resolution fluorescence in situ hybridization imaging [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Graph embedding is a dimensionality reduction strategy which transforms graph connectivity into distances in the embedding space 52,53 . It is known that the existence of hierarchically nested TADs in Hi-C matrix leads to strong clustering in the contact patterns 80,81 , and at the same time, power-law degree distributions of chromatin contact networks indicate the existence of node heterogeneity 12 . Strong clustering and node heterogeneity characterize a network with intrinsic flow hierarchy 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The size of TADs is almost positively correlated with the value of the single parameter, and small TADs from low value are usually positioned in large TADs from high value. Thinking TADs as a series of contiguous blocks on a chromosome, clustering iteratively merges TADs neighbors based on similarity of interactions between contact domains to a larger TAD until reaching a chromosome-arm size, and regards the layer-by-layer clustering relationship as the TAD hierarchies, including BHi-Cect 44 , SpectralTAD 45 , IC-Finder 46 , and TADpole 47 . This continuity is also manifested in graph theory, and its two big branches: network features (3DNetMod 48 , HBM 49 , GRiNCH 41 , and spectral 50 ) and structural entropy (deDoc 51 , and SuperTAD 40 ).…”
Section: Compendium Of Hierarchical Tad Callersmentioning
confidence: 99%